Watcher in the woods - Liparulo, Robert (Nashville, Tenn: Thomas Nelson, 2008)
Twelve-year-old David and his family search for their kidnapped mother in the many different time period portals of their home, but when a stranger appears and tries to force them to sell the house, their desperation reaches new heights.
Keywords: Time travel -- Fiction; Dwellings -- Fiction; Family life -- California -- Fiction; Horror stories; California -- Fiction